2019
DOI: 10.1002/mbo3.959
|View full text |Cite
|
Sign up to set email alerts
|

Co‐dynamics of Symbiodiniaceae and bacterial populations during the first year of symbiosis with Acropora tenuis juveniles

Abstract: Interactions between corals and their associated microbial communities (Symbiodiniaceae and prokaryotes) are key to understanding corals' potential for and rate of acclimatory and adaptive responses. However, the establishment of microalgal and bacterial communities is poorly understood during coral ontogeny in the wild. We examined the establishment and co-occurrence between multiple microbial communities using 16S rRNA (bacterial) and ITS2 rDNA (Symbiodiniaceae) gene amplicon sequencing in juveniles of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 92 publications
5
35
0
Order By: Relevance
“…As the microbiome is strongly associated to the coral holobiont, any disturbance in the host-Symbiodiniaceae relationship may have indirect effects on the microbial composition and its response to environmental and physiological factors. Other studies demonstrate the influence of Symbiodiniaceae on the host microbial community and also support the idea that these two components of the coral holobiont are finely tuned (Glasl et al, 2017;Grottoli et al, 2018;Littman, Bourne & Willis, 2010;Quigley et al, 2019). In the present study, Endozoicimonaceae were strongly positively correlated with the Symbiodiniaceae density in the tissue of A. tenuis and negatively correlated with NO − 2 /NO − 3 in A. millepora (see Fig.…”
Section: Explanatory Factors Of Tissue Microbiome Variationsupporting
confidence: 91%
“…As the microbiome is strongly associated to the coral holobiont, any disturbance in the host-Symbiodiniaceae relationship may have indirect effects on the microbial composition and its response to environmental and physiological factors. Other studies demonstrate the influence of Symbiodiniaceae on the host microbial community and also support the idea that these two components of the coral holobiont are finely tuned (Glasl et al, 2017;Grottoli et al, 2018;Littman, Bourne & Willis, 2010;Quigley et al, 2019). In the present study, Endozoicimonaceae were strongly positively correlated with the Symbiodiniaceae density in the tissue of A. tenuis and negatively correlated with NO − 2 /NO − 3 in A. millepora (see Fig.…”
Section: Explanatory Factors Of Tissue Microbiome Variationsupporting
confidence: 91%
“…Other studies demonstrate the influence of Symbiodiniaceae on the host microbial community and also support the idea that these two components of the coral holobiont are finely tuned (Glasl et al, 2017;Grottoli et al, 2018;Littman, Bourne & Willis, 2010;Littman, Willis & Bourne, 2009b;Quigley et al, 2019). In the present study, Endozoicimonaceae were strongly positively correlated with the Symbiodiniaceae density in the tissue of A. tenuis and negatively correlated with NO 2 -/NO 3in A. millepora (see Figure 5).…”
Section: Explanatory Factors Of Tissue Microbiome Variationsupporting
confidence: 90%
“…Manuscript to be reviewed harbors photosymbiotic dinoflagellates (family Symbiodiniaceae), that can provide up to 100% of energy required by their coral host (Muller-Parker, D'Elia & Cook, 2015). The Symbiodiniaceae community has been shown to vary in tandem with the bacterial community in early life stages of corals (Quigley et al, 2019) and this may be caused by the release of complex organic molecules such as the organosulfur compound dimethylsulfoniopropionate (DMSP; Bourne et al, 2013;Frade et al, 2016b). The coral tissue microbiome is mostly represented by bacteria belonging to the phyla Proteobacteria and Actinobacteria.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found that members of Lachnospiraceae, Rhodobacterales, and Caulobacterales, which include known diazotrophs [ 74 , 75 , 76 , 77 , 78 , 79 ], were relatively more abundant in corals subjected to light at night. These bacterial groups have also been found to co-occur with dinoflagellate symbionts of corals [ 80 , 81 ]. It is possible that the higher abundance of symbiont-associated microbes in the corals under ALAN treatment is linked to the greater abundance and activity of the dinoflagellate symbionts.…”
Section: Discussionmentioning
confidence: 99%